Cardiotoxicity Caused by 5 Fluorouracil in a Patient with Adenocarcinoma of Colon - Deo, Rajeeb Kumar; Khatri, Rishi; Khatri, Devendra; Karki, Binod (Medical Journal of Shree Birendra Hospital, 2013)
From the time of inception, various chemotherapeutic agents are known to cause cardiotoxicity. The cardiotoxicity ranges from mild transient abnormality to irreversible cardiac tissue damage. Certain classes of drugs like anthracyclines are known to be cardiotoxic while some newer drugs like Transtuzumab also cause cardiotoxicity. 5 Fluorouracil is known to be cardiotoxic though the incidence is low. We present a case of cardiotoxicity due to prolonged 5 Fluorouracil infusion in a patient with adenocarcinoma of colon. Medical Journal of Shree Birendra Hospital; January-June 2013/vol.12/Issue1/43-46 DOI: http://dx.doi.org/10.3126/mjsbh.v12i1.9094